Experimental Investigation on Combustion, Performance, Emissions, and Vibrations in a Diesel-Hydrogen Dual-Fuel Engine with an On-Demand Hydrogen Generation System - Shaik Subani; Domakonda Vinay Kumar; Shaik, Farooq; Noor Alam (International Journal of Integrated Engineering, 2025)
The study addresses the challenge of onboard hydrogen storage in transportation by proposing an innovative solution involving an on-demand hydrogen generation system. This system operates via a chemical reaction between aluminum sulphate (Al₂(SO₄)₃) and sodium borohydride (NaBH₄), producing hydrogen gas in real-time. The research examines the performance of a Variable Compression Ratio (VCR) diesel engine running in a dual-fuel mode, where hydrogen is supplied from the reactor. Engine behaviour was systematically analyzed under varying operating conditions, including compression ratios of 16, 17, and 18, and engine loads ranging from no load up to 12 kg, increasing in 3 kg steps. Additionally, the hydrogen flow rate was adjusted between 0 and 15 liters per minute. The results indicate that the engine achieved its best performance, in terms of efficiency, combustion, emissions, and vibration characteristics, at a compression ratio of 18 and a hydrogen flow rate of 15 liters per minute. These findings offer valuable insights for the advancement of on-demand hydrogen reactors, highlighting their potential for integration with VCR diesel engines to promote cleaner and more sustainable transport solutions.